Pengaruh Faktor Internal Dan Eksternal Perusahaan Terhadap Audit Delay Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Tahun 2009 – 2011 - Mega Purnama Santosa; Ratnawati Kurnia (Universitas Multimedia Nusantara, 2013)
Company need public accountant for auditing financial statement. Auditor professionalism needed for auditing and criteria of professional auditor is timeliness for audit report. Timeliness can be affected audit delay. Object in this research is companys listed in Bursa Efek Indonesia (BEI) for the period 2009 – 2011. This research examined the effect of size company, age, profitability, size public accountant, auditor change, and auditor opinion. This method in this research study is causal. Data analysis techniques using multiple linear regression. These result indicate that size public accountant and auditor opinion significantly influence audit delay, but size company, age, profitability, and auditor change no significant on audit delay. Size company, age, profitability, size public accountant, auditor change, opinion auditor have significant influence to audit delay. Keywords: size company, age, profitability, size public accountant, auditor change, audit opinion, audit delay.